2023
DOI: 10.5811/westjem.60587
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Factor-Xa Inhibitor-associated Bleeding with Andexanet Alfa or 4 Factor PCC: A Multicenter Feasibility Retrospective Study

Adam J. Singer,
Mauricio Concha,
James Williams
et al.

Abstract: Background There are no randomized trials comparing andexanet alfa and 4 factor prothrombin complex concentrate (4F-PCC) for the treatment of factor Xa inhibitor (FXa-I)-associated bleeds, and observational studies lack important patient characteristics. We pursued this study to demonstrate the feasibility of acquiring relevant patient characteristics from electronic health records. Secondarily, we explored outcomes in patients with life-threatening FXa-I associated bleeds after adjusting for thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this sense, the results of Ammar et al [ 15 ] showed that mortality was the same for both treatment groups at 38% and 36% for 4F-PCC and AA, respectively. Pham et al [ 22 ] and Lipski et al [ 19 ] also presented similar results. While Pham et al [ 22 ] observed an overall mortality of 34% and 21% for AA and 4F-PCC, respectively, Lipski et al [ 19 ] presented mortality data up to a follow-up period of 28 days (AA = 39.1; 4F-PCC: 40.4), although this period did not reveal any statistical differences in mortality.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…In this sense, the results of Ammar et al [ 15 ] showed that mortality was the same for both treatment groups at 38% and 36% for 4F-PCC and AA, respectively. Pham et al [ 22 ] and Lipski et al [ 19 ] also presented similar results. While Pham et al [ 22 ] observed an overall mortality of 34% and 21% for AA and 4F-PCC, respectively, Lipski et al [ 19 ] presented mortality data up to a follow-up period of 28 days (AA = 39.1; 4F-PCC: 40.4), although this period did not reveal any statistical differences in mortality.…”
Section: Resultssupporting
confidence: 58%
“…In contrast, in the data of Vestal et al [ 24 ], Pham et al [ 22 ] and Oh et al [ 20 ], the number of thrombotic events was higher in the group receiving 4F-PCC, with more than 80% of them related to cerebral ischemia and DVT. Lipski et al [ 19 ] also reported a greater number of thromboembolic events with the use of 4F-PCC (8 events) than with AA (5 events), which were related to deep vein thrombosis/pulmonary embolism.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations